2016
DOI: 10.1021/acs.cgd.6b00874
|View full text |Cite
|
Sign up to set email alerts
|

Near-Infrared Upconversion Transparent Inorganic Nanofilm: Confined-Space Directed Oriented Crystal Growth and Distinctive Ultraviolet Emission

Abstract: A well-designed, efficient, one-step assembly strategy is implemented in this work by constructing a confined nanospace to manufacture an approximately 120 nm thick inorganic upconversion (UC) nanofilm with highly (101) oriented and morphology-controllable crystal grains, as well as transparent and robust characteristics. The morphology and distribution density of crystal grains of the film can be tuned by varying space heights and precursor concentrations. The confined space incubates a stable growing environ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 44 publications
2
1
0
Order By: Relevance
“…Despite their large thickness, all layers are fairly transparent in the visible range, with values of ∼90% from far-red on, as shown in Figure 2 d. Yet, transmittance reduces up to 70% at short wavelengths, especially for films annealed at high temperature, suggesting a larger fraction of scattered light, due to some nanoparticle clustering. 47 It is noteworthy that transparency values attained surpass that of any previous report, 1 , 34 , 60 , 61 and similar figures have been only observed in extremely thin layers (∼100 nm), 62 or in polymer films with low filling fraction of nanophosphors. 10 , 33 Importantly, transmittance of our UC films feature a dip at ∼950 nm, as shown in the inset of Figure 2 d. Indeed, absorptance measurements displayed in Figure 2 e confirm absorption bands associated with the 2 F 7/2 – 2 F 5/2 transition of Yb 3+ ions at ∼950 nm.…”
Section: Results and Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Despite their large thickness, all layers are fairly transparent in the visible range, with values of ∼90% from far-red on, as shown in Figure 2 d. Yet, transmittance reduces up to 70% at short wavelengths, especially for films annealed at high temperature, suggesting a larger fraction of scattered light, due to some nanoparticle clustering. 47 It is noteworthy that transparency values attained surpass that of any previous report, 1 , 34 , 60 , 61 and similar figures have been only observed in extremely thin layers (∼100 nm), 62 or in polymer films with low filling fraction of nanophosphors. 10 , 33 Importantly, transmittance of our UC films feature a dip at ∼950 nm, as shown in the inset of Figure 2 d. Indeed, absorptance measurements displayed in Figure 2 e confirm absorption bands associated with the 2 F 7/2 – 2 F 5/2 transition of Yb 3+ ions at ∼950 nm.…”
Section: Results and Discussionsupporting
confidence: 64%
“…Yet, transmittance reduces up to 70% at short wavelengths, especially for films annealed at high temperature, suggesting a larger fraction of scattered light, due to some nanoparticle clustering. 47 It is noteworthy that transparency values attained surpass that of any previous report, 1,34,60,61 and similar figures have been only observed in extremely thin layers (∼100 nm), 62 or in polymer films with low filling fraction of nanophosphors. 10,33 Importantly, transmittance of our UC films feature a dip at ∼950 nm, as shown in the inset of Figure 2d.…”
Section: ■ Results and Discussionsupporting
confidence: 59%
“…15 It has been reported that quantum yields of the (101) oriented NaYF 4 :Yb 3+ /Er 3+ nanofilms grown through constructing a confined nanospace are 4.7 and 16.1 times higher than those of UC nanoparticles synthesized by typical thermal decomposition method and hydrothermal method, respectively. 16 Therefore, to grow oriented hexagonal phase NaGdF 4 :Eu 3+ films with higher conversion efficiency through a simple process is highly interested.…”
mentioning
confidence: 99%